A new species of Hohenbuehelia (Pleurotaceae) from India - Bijeesh, C.; Kumar, A. Manoj; Pradeep, C.k.; Vrinda, K.b. (Phytotaxa, 2019)
Hohenbuehelia odorata sp.nov. is described based on morphological and molecular data of the nuclear ribosomal internal transcribed spacer (nrITS) region from Kerala State, India. The macro- and micromorphological features in conjunction with nrITS-based phylogenetic analysis performed using Maximum Likelihood (ML) method supported the novelty of H. odorata. Complete morphological descriptions, photographs and comparisons with similar species and a key to the Indian species of Hohenbuehelia are provided.